DESIGN OF STANDARDS INTEGRATION OF QUALITY MANAGEMENT CERTIFICATION INSTITUTIONS, PRODUCT CERTIFICATION INSTITUTIONS, AND GREEN INDUSTRY CERTIFICATION IN BALAI BESAR KEMENTERIAN PERINDUSTRIAN - Destiyani, Pristi
Implementing more than two management systems provides many benefits for an organization. However, this can result in more workload, time, and process requirements that must be carried out by institutional or organizational managers at the same time. Therefore, a method is needed to simplify the management of a management system with many standards. An integrated management system makes it possible to streamline an organization's processes, align all standard requirements, reduce internal audit time and costs, and reduce document duplication compared to a management system implemented alone. Therefore, the implementation of integrated quality management systems can have a substantial impact on the way organizations are managed with many standards. Choosing the right integration method will increase the success of the standard management system integration process. This research aims to produce a formulation of integration steps and management system design based on the management system standards of quality system certification institutions (SNI ISO/IEC 17021:2015), Product certification institutions (SNI ISO/IEC 17065:2012), and green industry certification institutions (Permenperin No. 39 of 2018). This study uses a qualitative method. An integrated management system is created to be allied in all situations in all processes at the Certification Body. Integration measures are obtained by combining three reference methods. The integrated management system (quality guidelines) is verified and validated by experts using a peer review method based on Johannsen's reference structure verification method (2013). Implementation of the design is carried out at the BBSPJIT certification body, a work unit at the Ministry of Industry. The results of the research are the formulation of steps for designing integrated management systems for certification bodies that simultaneously apply standards and quality guidelines. It is hoped that quality guidelines can be implemented in certification bodies that implement the standards of certification bodies for quality management systems, products, and green industries throughout Indonesia.